2022
DOI: 10.1007/s10943-022-01695-2
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Well-Being and Care Burden in Caregivers of Patients with Breast Cancer in Turkey

Abstract: This research was carried out to identify the relationship between the spiritual well-being and caregiver burden in caregivers of patients with breast cancer. The study was conducted with family caregivers of patients with breast cancer who presented to the oncology clinic of a university hospital for treatment. The study sample included a total of 138 family caregivers who met the criteria for participation and agreed to participate in the study. The data were collected using a participant information form, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Consistent with the current conclusion, recent research by Torabi Chafjiri et al found that caregivers of elderly individuals with stroke in Iran experienced less stress when they had a spiritual outlook 40 . Previous studies has also found a negative correlation between spiritual well‐being and caregiving responsibilities 26,50 . One aspect of spirituality illustrated here is that of spiritual wellness.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the current conclusion, recent research by Torabi Chafjiri et al found that caregivers of elderly individuals with stroke in Iran experienced less stress when they had a spiritual outlook 40 . Previous studies has also found a negative correlation between spiritual well‐being and caregiving responsibilities 26,50 . One aspect of spirituality illustrated here is that of spiritual wellness.…”
Section: Discussionsupporting
confidence: 90%
“… 40 Previous studies has also found a negative correlation between spiritual well‐being and caregiving responsibilities. 26 , 50 One aspect of spirituality illustrated here is that of spiritual wellness. Care providers for chronic patients, in particular, can benefit from attending to their spiritual well‐being to cope with the stresses inherent in their duties.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, caregivers with higher spiritual intelligence may be more resilient, something which may help them better manage caregiving challenges and experience lower levels of care burden. Another study analyzed the effects of spirituality on care burden and the quality of life in informal caregivers of older adults and showed that higher levels of spirituality were associated with lower care burden and better quality of life (41). The results of both studies emphasized that spirituality had an inverse relationship with care burden and improved the quality of life and coping skills among caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…The role of home nursing and family‐centred care is crucial in improving the quality of life for breast cancer patients, a concept widely recognized in both Chinese and international contexts (Leung et al., 2014; Mokhtari‐Hesari et al., 2018; Segrin et al., 2020; Townsend et al., 1990; Zhao et al., 2022). However, the increasing burden and psychological distress faced by family caregivers as a patient's condition worsens is a global concern, mirrored in China's experience (Bahrami & Farzi, 2014; Türkben Polat & Kiyak, 2023). The tendency to overlook caregiver burden in clinical practice is a worldwide issue, not limited to any single cultural or healthcare setting (Adelman et al., 2014; Giunta et al., 2022).…”
Section: Introductionmentioning
confidence: 99%